Effect of high-pressure processing (HPP) on production and characterization of chia seed oil nanoemulsions. (April 2021) - Kaya, Eda Ceren; Oztop, Mecit Halil; Alpas, Hami
Abstract: Chia seed is a good source of protein, carbohydrate, fat, dietary fiber, antioxidants and contain poly unsaturated fatty acids (PUFA) higher than any other seed-based food sources. In this study, the extracted oil from chia seed by conventional and high pressure processing (HPP) extraction was used to prepare nanoemulsions. The spontaneous emulsification was approached at six concentrations (0.5, 1, 1.25, 1.5, 2.5 and 3% (w/w)) and four different surfactants to oil ratio (1, 2, 3 and 4 (w/w) SOR). Some characteristics such as mean droplet size, antioxidant activity, total phenolic content, peroxide value, instantaneous and long-term stability, oil-water interaction and secondary oxidation products were assessed. According to the results, formulated nano emulsions had higher phenolic content and antioxidant activity than the corresponding oil samples. The highest antioxidant activity, phenolic content and oxidative stability were associated with emulsion samples prepared with 2.5% (w/w) chia oil. Highlights: Chia seed oil nanoemulsions were prepared by spontaneous emulsification. Six different oil concentrations (0.5, 1, 1.25, 1.5, 2.5 and 3% (w/w)) and four different SOR (1, 2, 3 and 4 (w/w)) were used. Ratio of surfactant to oil significantly affects the antioxidant activity of emulsions. The nanoemulsions prepared with 2.5% (w/w) oil showed the highest antioxidant activity.